1994
DOI: 10.2535/ofaj1936.71.2-3_99
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Anatomy of the Internal Mammary Lymphatics in the Superior Mediastinum and Anterior Mediastinal Lymph Nodes

Abstract: The lymphatics lying along the internal thoracic artery and vein, which are termed the "internal mammary lymphatics" (IML), were minutely dissected in 134 adult cadavers (80 males and 54 females, aged 27-94 years) in order to clarify the configuration of IML in the superior mediastinum. On the right side, IML frequently terminated at the brachiocephalic angle (BA) nodes and often at the nodes situated at an intermediate position between the internal thoracic artery and vein. By way of these nodes, IML communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The internal mammary nodal chain has previously been studied . Stibbe published an outstanding gross anatomic description of the internal mammary nodes in 1918, based on dissection in 60 cadavers .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The internal mammary nodal chain has previously been studied . Stibbe published an outstanding gross anatomic description of the internal mammary nodes in 1918, based on dissection in 60 cadavers .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports on endoscopic internal mammary lymph node dissections with and without harvest of adjacent vessels have been published; this may represent a minimally invasive approach to VLNT donor sites. The entire dissection can be completed in 70 min via three trocar sites in the lateral chest wall . One study of complete unilateral internal mammary nodal chain dissection demonstrated that an average of 4.6 nodes can be removed .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissection of the lymphatics was performed under direct eyesight with the aid of a binocular microscope, according to the Deki and Sato21 procedure. In addition, clearing methods, to identify finely intercalated nodes and valves, and the histological examination of vessel terminals and lymph nodes were performed case‐by‐case, as reported previously 22,23. Injection of a water‐soluble resin24 into the portal vein system and inferior vena cava was also performed in 10 of 15 specifically prepared cadavers before treatment with 10% formalin solution, to easily discriminate lymph vessels from fine venous tributaries.…”
Section: Methodsmentioning
confidence: 99%